Worse than cell lysis: The resilience of Oscillatoria sp. during sludge storage in drinking water treatment. (1st October 2018) - Sun, Jiongming; Xu, Hangzhou; Pei, Haiyan; Jin, Yan; Li, Hongmin; Ma, Chunxia
Abstract: Benthic Oscillatoria sp. may form dense surface blooms especially under eutrophic and calm conditions, which poses a threat to drinking water safety because it can produce toxic and odorous metabolites. This is the first study to investigate the effect of the conventional coagulant polyaluminium ferric chloride (PAFC) on removal of Oscillatoria sp., and the behavior of Oscillatoria sp. cells in sludges formed from different dosages of PAFC (control, optimum, and overdose system) during storage was also studied. Oscillatoria sp. cells can be removed efficiently by coagulation of PAFC. The adverse environmental stresses of sludge, such as lack of light and anoxic environment, decrease cell viability and induce the increase of superoxide dismutase activity (SOD) and malondialdehyde content (MDA) in Oscillatoria sp. cells during the first 4 days. Because Oscillatoria sp. can adapt to the low-light and hypoxic circumstances in sludge gradually, the cells regrow with prolonged storage time. Compared to planktonic Microcystis aeruginosa and Cylindrospermopsis raciborskii, regrowth of Oscillatoria sp. during storage may present a bigger threat, even though Microcystis aeruginosa and Cylindrospermopsis raciborskii cells will be damaged and release toxic compounds. Growth rates of algae in coagulated systems were lower than that in control system because of the restriction of flocs. It is worth noting that the chlorophyll a level was increased by a factor of 3.5 in the optimal-dose system, and worse, the overdose system increased by a factor of 6 in chlorophyll a after 8 d storage due to the benefit of higher Fe levels. Concentrations of extracellular geosmin and cylindrospermopsin also increased during storage, especially after 4 d, and varied in the following sequence for a given storage duration: control system > overdose system > optimum system. Overall, due to decrease of SOD and MDA in Oscillatoria sp. cells after 4 d storage, algae cells regrew rapidly, especially in overdose system. Hence, sludge should be treated within 4 d and excess PAFC dosing should be avoided. Graphical abstract: Highlights: Oscillatoria sp. was coagulated and removed effectively with 5 mg/L PAFC. Oscillatoria sp. exhibited vigorous proliferation during floc storage. 5 mg/L PAFC limited growth of Oscillatoria sp. and release of CYN and GSM. Oscillatoria sp. flocs are more detrimental to environment than other species. Sludges containing Oscillatoria sp. should be handled within 4 days.